(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Social networks have infiltrated many domains of educational practices or procedures, in addition to providing amusement and information. Nowadays, social media has an ever increasing impact on the lives of youngsters. This paper attempts to emphasize the usage of the social network in the advanced education while also highlighting some of the elements at play. Furthermore, through a analysis of related article, people hope to provide visions into social networks effects on (a) active learnings (assistances, educational development, teamwork’s, or coordination enhancement, educational achievements) from perspectives of students or educator, (b) consumers’ personalities profiles or learnings styles, (c) social networking site online learnings (LMS) learning managements systems, (d) their usage in the advanced education. The findings show positive effects in all of the aforementioned areas, demonstrating that the usage of the online social network in higher learning has a bright future. Teachers or higher education institutions, on the other hand, have not yet been sufficiently mobilized to leverage online social networks in their operations. The future aspects of new media have been attracting the interest of mass seekers around the world. As a result, the leading colleges have begun providing skill and industry-focused programs.